Richard Mather of Dorchester - Burg, B. R. (Barry Richard), 1938- (The University Press of Kentucky, 1976)
Mather is a well-known name in the persons of Increase and Cotton Mather. Here for the first time is a biography of the father and grandfather, respectively, of those two great figures of the seventeenth and eighteenth centuries. Richard Mather left few personal records of his life in the form of letters, diaries, or autobiographical writings. In his research, Mr. Burg sought out little used ecclesiastical records in England, pieced together events from inferences and deductions, and analyzed by sociological, psychological, and anthropological methods the life of this seventeenth-century divine.